Foreign Market Subsidiary Mandates A Select and Temporary MNC Phenomenon? - Lohr, Nicolas. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Internationalization processes have long been a core topic of International Business research. Very little focus, however, was thereby put on how foreign subsidiaries themselves internationalize. Nicolas Lohr investigates how foreign subsidiaries of multinational corporations expand their presence and functional scope into foreign territories. Multiple case-studies based on in-depth interviews with HQ and subsidiary management suggest that subsidiary internationalization represents a select MNC phenomenon. Foreign subsidiaries only appear to receive cross-border responsibility if their value proposition for overcoming liability of inter-regional foreignness is capable of more than offsetting any risk increase that stems from principal-agent relationships between corporate headquarters and foreign subsidiaries. After attaining the initial mandate, the subsidiary’s restrained access to HQ-like functions, intra-MNC competition and altering localization degrees in the market covered by the mandate puts the sustainability of cross-border responsibilities at risk. As a consequence, the internationalization of foreign subsidiaries often follow discontinuous rather than gradual evolutionary trajectories. In addition, cross-border subsidiary mandates appear to be pre-defined and temporary in nature. As a result, they may have a limited life span from their very conception.   Contents   ·         Subsidiary Internationalization ·         Subsidiary mandates ·         Principal-agent relationships   Target Groups ·         Researchers and students of International Business studies ·         Sales managers, CEOs of foreign subsidiaries   The Author Nicolas Lohr earned his doctorate from the University of Fribourg in Switzerland and received an MSc degree from the ESCP Europe in France. He’s a consultant with an international management consulting firm.